2023
DOI: 10.1159/000528770
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Inflammatory Markers in Clinical High Risk of Developing Psychosis

Abstract: <b><i>Introduction:</i></b> Immune alterations are associated with the progression of psychosis. However, there are few studies designed to longitudinally measure inflammatory biomarkers during psychotic episodes. We aimed to assess changes in biomarkers from the prodromal phase to psychotic episodes in individuals with clinical high risk (CHR) of psychosis and compare converters and non-converters to psychosis as well as healthy controls (HCs). <b><i>Methods:</i></… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The occurrence and development of psychosis is not only a change in behavioral appearance or brain function but also a characteristic change in the characteristics of immunoinflammatory markers in the early stage. The SHARP team 29,34,35 found that the imbalance of The results suggest that antipsychotic drugs should not be used prematurely in the at-risk population 27,28,40 as they are only valuable for <15% of the CHR population of a certain subtype [41][42][43] ; it is necessary to carry out individualized new intervention technologies for CHR subtypes of different biological dimensions. 3 Approximately 30% of the CHR population may recover naturally without intervention, and a large proportion of CHR are teenagers.…”
Section: Immune Dimension Of Inflammatory Cytokines and Complement Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of psychosis is not only a change in behavioral appearance or brain function but also a characteristic change in the characteristics of immunoinflammatory markers in the early stage. The SHARP team 29,34,35 found that the imbalance of The results suggest that antipsychotic drugs should not be used prematurely in the at-risk population 27,28,40 as they are only valuable for <15% of the CHR population of a certain subtype [41][42][43] ; it is necessary to carry out individualized new intervention technologies for CHR subtypes of different biological dimensions. 3 Approximately 30% of the CHR population may recover naturally without intervention, and a large proportion of CHR are teenagers.…”
Section: Immune Dimension Of Inflammatory Cytokines and Complement Pr...mentioning
confidence: 99%
“…The occurrence and development of psychosis is not only a change in behavioral appearance or brain function but also a characteristic change in the characteristics of immunoinflammatory markers in the early stage. The SHARP team 29 , 34 , 35 found that the imbalance of inflammation (CD4 + T helper cell [Th] 1/Th2 cytokine imbalance) was related to psychotic attack in the CHR outcome after studying the balance of inflammatory factors in the peripheral serum of the CHR population. The baseline serum Th1 inflammatory factor concentration in the CHR‐C group was significantly reduced, and can be considered a form of immune deactivation, resulting in a lower Th1/Th2 ratio than that in the CHR‐NC and HC groups.…”
Section: Shanghai At Risk For Psychosis (Sharp)mentioning
confidence: 99%
“…In the context of neuropsychiatric disorders such as psychosis, there is growing evidence to indicate a pivotal role for inflammation in the pathogenesis of psychotic onset. [1][2][3] Neuroinflammation is characterized by the activation and proliferation of glial cells, 4,5 particularly microglia and astrocytes, within the central nervous system, which triggers an inflammatory response in the brain. 5 Under abnormal conditions, such as in brain disease, microglia transition from a "resting" state to an "activated" state, releasing proinflammatory cytokines like interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α.…”
mentioning
confidence: 99%
“…The levels of interleukin factors appear to be associated with the course of the disease and the severity of symptoms. Patients with elevated levels of IL-6, IL-8, and IL-4 tend to have a longer duration of illness and longer hospital stays (17,18). Moreover, higher levels of IL-6, IL-1b, IL-33, and IL-17 are associated with more severe positive symptoms (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%